Kelangsungan Pendidikan Agama Islam di Negara Sekuler: Madrasah di Singapura - Samuri, Samuri (YASIN, 2022)
This paper explores how Islamic madrasahs changed the minds of their students by teaching both religious and academic subjects. This comes alongside examining how these schools created racial and religious cohesiveness outside the boundaries of traditional conservatism and extremism. This research is qualitative, meaning it uses a variety of methods to gather its findings. This paper examines the negative effects of Madrasas on economic development in Singapore. It looks at historical methods for gathering data and literature from its research. Some specific data analyzed and presented in the paper includes relevant literature and information gathered by these methods. Before 2001, the Singaporean government pushed to close traditional or conservative schools of religious learning. They considered traditional madrasas a source of religious and racial strife that impeded cohesion among the races and religions in their country. Islamic education in Singapore can be observed through three phases. The first is the colonial phase where a secular system was adopted. After the country was no longer colonized, a traditional system was implemented. Currently, the third phase has begun where an integrated curriculum is in use.